2020
DOI: 10.2528/pierc20010203
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Only Nulling With Limited Number of Controllable Elements

Abstract: In this paper, the required array patterns with controlled nulls are obtained by optimizing only the excitation phases of a small number of elements on both sides of the array. A genetic algorithm is used to appropriately find which elements of the array to be optimized and also to find the required number of the excitation phases. The performance of the proposed phase-only method is compared with some other exciting methods, and it is found to be competitive, fulfil all the desired radiation characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Figure 1 shows the right side of the general structure of the standard linear array that consists of N elements, then the standard array factor (AF) in the far field can be written as [3]:…”
Section: Model Of Multi-objective Function With Thinned Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the right side of the general structure of the standard linear array that consists of N elements, then the standard array factor (AF) in the far field can be written as [3]:…”
Section: Model Of Multi-objective Function With Thinned Methodsmentioning
confidence: 99%
“…The elimination of radiating components from a regularly spaced or cyclic array to generate the desired radiation pattern is referred to as array thinning. The main objective of thinning is to reduce the weight, cost, energy consumption, and execution time of the algorithm [1][2][3]. The locations of the radiating elements will be determined in thinning array synthesis, and each element will have two states: "ON component" or "active state" (when the element is supplied) and "OFF component" or "passive state" (when the elements are passively removed or not fed by the source) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In [8], the authors suggested to adjust only the amplitude excitations of the array elements instead of both amplitude and phase excitations to simplify the design implementation of the array feeding network and reduce the number of the optimized variables. Other researchers suggested the use of the phase-only excitation method [9] to optimize the planar array elements. Recently, efficient methods for linear [10][11][12][13][14] and planar arrays [15][16][17][18] were suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Such operation results in a significant improvement in the output signal-to-interference plus noise ratio (SINR). Historically, all the element excitations have had their amplitude weighting [1] and/or phase weighting [2,3] adjusted in order to achieve null steering [4] or sidelobe level (SLL) reduction [5,6]. Other methods use two edge elements control [7] or a restricted subset of the array elements [8].…”
Section: Introductionmentioning
confidence: 99%